(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Through a writing-in-route, the article presents some of the author’s experiences during “Amazônia centro do mundo”, an event that, over three days, brought together indigenous leaders, researchers and activists in Altamira (PA), city where the world’s second largest hydroelectric power plant was build. The text is stitched together with Altamira 2042, a piece by Gabriela Carneiro da Cunha, aiming to argue that when the institutions prove incapable of repairing the irreparable, art can assume the responsibility of instituting other imaginations in those who share the artistic work.